Creative Chronography in Early Christianity: John Malalas on the Deaths of King Cyrus of Persia - Djurslev, Christian Thrue (Vigiliae Christianae, 2025)
In this article, I use John Malalas’ account of Cyrus’ two deaths – which he claimed was based on Pythagoras of Samos and Julius Africanus – as a case study for historiographical creativity in early Christian chronography. First, I detect that one of Cyrus’ deaths is calqued on Xerxes’ death in the Greek historian, Ctesias of Cnidus, and thus an original interpretation of the event. Second, I place this death story in the greater context of Malalas’ account, showing the great extent to which Malalas, or his source, has rewritten the story of Cyrus. Third, I test the death story’s attribution to Julius Africanus, which I argue is false, based on the high level of chronographic accuracy required for Africanus’ Chronographiae. Fourth and finally, I examine how Malalas was using Africanus’ authority to authenticate the dubious death story of Cyrus.